Regional variation in cerebral oxygen metabolism during acute severe hypoxia with temporary cognitive impairment - Daehun Kang; Koji Uchida; Clifton R. Haider; Norbert G. Campeau; Myung-Ho In; Erin M. Gray; Joshua D. Trzasko; Kirk M. Welker; Jeffrey L. Gunter; Matt A. Bernstein; Max R. Trenerry; David R. Holmes, III; et al. (NeuroImage)
Acute exposure to severe hypoxia impairs cognitive performance, yet the integrated brain mechanisms underlying this temporary decline remain unclear. This study examined regional variations in cerebral oxygen metabolism during acute hypoxia and their relationship to cognitive impairment. Eleven young, healthy participants (26.5 ± 4.5 years old) performed the Go/No-Go task during two sessions, each of which includes three minutes of hypoxia (FiO2 = 7.7 %). Cerebral blood flow (CBF) was assessed using pCASL MRI in one session, while blood-oxygen-level-dependent (BOLD) signals were acquired in another. Fractional changes in CBF (δCBF) and BOLD (δBOLD) were combined using a modified Davis model, adjusted for physiological differences between normoxia and acute and severe hypoxia, to calculate the fractional change in cerebral metabolic rate of oxygen (δCMRO2). Group-level z-normalized δCMRO2 maps revealed significant regional heterogeneity, with most pronounced reductions in areas associated with the dorsal and ventral attention networks and executive frontoparietal networks. These regions exhibited δCMRO2 reductions exceeding the hemispheric average (-9.6 ± 7.9 %) and were associated with increased commission errors during the Go/No-Go task, reflecting impaired inhibitory control and sustained attention. This study highlights the brain's adaptive prioritization of certain networks under oxygen deprivation, providing insights into the physiological mechanisms underlying hypoxia-induced cognitive impairments. These findings enhance our understanding of how acute hypoxia affects brain function, emphasizing the importance of network-specific adaptations in maintaining cognitive performance during oxygen deprivation.